Development of Macroeconomic Theory Materials Based on Blended Learning - Putri Sari M. J. Silaban; Joko Suharianto; Dede Ruslan (BIRCU, 2020)
The aim of the study was to produce teaching material for Macroeconomics Theory. The Research and Development (R&D) method by Borg and Gall was used in this study. The population of this study was all Economic Education Study Program’s students who took Macroeconomics courses in 2019. The sample was determined by using the purposive random sampling principle and the sample class made for the implementation and limited testing of small sample was Class C of Economic Education. Based on the result of the study, it was decided that the teaching material for Macroeconomics Theory that has been validated by 2 expert validators had a very high level of eligibility (88.75%) provided revisions were needed. After it has been fully revised, the material was tested to all 30 students of Class C of Economic Education during Macroeconomics Theory course. Based on the testing conducted to the small sample, it showed that there was a significant improvement of the learning outcomes before and after the blended-learning based teaching material was implemented. The result was all the user-friendliness, usability, and time effectiveness factor have an average value ≥4. It can be concluded that the book being developed has met the readability and practicality criteria. The study was only conducted up to stage 7 -producing the teaching material of revision draft.